Accelerating the Competitiveness of Banjarsari Village Tape Industry Products Through Training and Diversification of Tape Smoothies Products with Potential for Income Generating - Salsabila, Annisa Ayu; Surya, Eka Putri; Aruna, Alby; Prasetyo, Abdul Rahman; Marcelliantika, Adinda (Civiliza Publishing, 2024)
The acceleration of the competitive edge of the tape industry in Banjarsari Village through training and product diversification of income-generating Tape Smoothies aims to enhance local producers' skills and knowledge in creating innovative products. This program involves technical training in the production of Tape Smoothies, combining tape with smoothie ingredients to create a healthy and delicious beverage. Methods include workshops, live demonstrations, and production outcome evaluations. Results show a significant improvement in production skills and innovation capabilities of local producers. The implementation of this program is expected to support product diversification, increase competitiveness, and expand the market for tape products in Banjarsari Village.